(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2020)
We have studied Single donor transistors with designed nanochannels in which the tunnel barrier height is enhanced due to dielectric confinement. For single electron tunneling effects the charging energy is significantly large. Which is a first limiting factor for shallow dopants? At high temperatures, thermally activated transport became quickly dominant. We have found that at high temperature operation of electron tunneling occurred via a single donor. We have found that the single dopant devices operating at room temperature paving the way for practical applications based on individual dopant atom in silicon nanodevices. We have also found that in nanopatterned channel transistors, single electron tunneling via individual positive donors was observed at elevated temperatures. The obtained results were found in good agreement with previously obtained results.